An investigation of the factors influencing passengers' ability to operate exits on civil aircraft - Mills, Ann Martine (Cranfield University, 1999)
Type III exits are a useful means of escape and they exist on a large proportion of the airline fleet. Evidence from aircraft accidents and previous research indicates that many passengers experience great difficulty in operating and evacuating through an overwing exit. There are two different approaches to improving passenger operating performance; these being improvement and simplification of the task itself or provision of clear instruction or practice for the passenger seated next to the exit. The first experiment investigated the impact of improvement to the Type III exit mechanism and practice on participant operation speed and accuracy. The results of a four-way Analysis of Variance indicated that both speed and accuracy of operation improved as a result of the exit redesign. A Repeated Measures Analysis of Variance also showed that the provision of practice led to a significant reduction in operation times. However, practising the operation of the current design of the Type III exit failed to improve participant speed of operation to the level achieved by participants when operating the modified exit for the first time. The results from the second study which investigated the impact of variations in safety briefings on participants' speed and accuracy of operation of the traditional Type III exit clearly indicated the benefits of providing some form of instruction. Allowing participants to watch a `fellow passenger' on a video performing the task led to quicker and more accurate exit operation. Variations in pre-flight briefing card design were also shown to improve operation accuracy. The implications of these results for the future development of self help exits, provision of training and design of briefing material are discussed.